Photoredox-Catalyzed Decarboxylative C–H Acylation of Heteroarenes - Jia, Wei; Jian, Yong; Huang, Binbin; Yang, Chao; Xia, Wujiong (Synlett, 2018)
A mild, environmentally friendly, and regioselective acylation of heterocycles with inexpensive carboxylic acids is reported via photoredox catalysis. The strategy is highlighted with good functional group tolerance and substrate scope which could rapidly realize the acylation of various heterocyclic compounds.
Keywords: 2,2-diethoxyacetic acid; α-keto acids; heterocycles; C–H functionalization; acylation